2016
DOI: 10.1590/s0100-736x2016000700017
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de diferentes concentrações de melatonina em espermatozoides de carneiros sobre estresse oxidativo após criopreservação

Abstract: ABSTRACT.-Souza W.L., Moraes E.A., Costa J.M.S., Souza P.H.F., Lopes Junior E.S., Oliveira R. The aim was to evaluate the effect of adding different concentrations of melatonin in ram semen diluted after cryopreservation. Ten ejaculates were collected0 from three adult ram (n=30) by means of artificial vagina for sheep. The collected samples were diluted in Tris-egg yolk, to a final concentration 200x10 6 sptz/mL kept in water bath at 32°C, and melatonin added as treatments: control; 100pM; 100nM; 100μM and 1m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
2
0
5
Order By: Relevance
“…Succu, et al (2011) have indicated that supplementing melatonin in a dose of 1.0 mM to ram extender maintained progressive motility, intracellular ATP concentrations, DNA integrity and fertilization rate in comparison to other doses (0.001, 0.01, 0.1, and 10 mM). In contrast, Souza et al (2016) have stated that low concentration of melatonin (100 pM) increased the sperm motility, mitochondrial activity, integrity of plasma membrane and acrosome in ram semen in comparison to high concentrations (100 nM, and 100 μM). Moreover, supplementation of melatonin at low dose (0.1 mM) to semen extender of buffalo bulls maintained the ultrastructure integrity of the sperm and increased pregnancy rate in compared to control and high doses groups (0.250, 0.500, 0.750 and 1 mM) (EL-Raey et al, 2015).…”
Section: Discussionmentioning
confidence: 87%
“…Succu, et al (2011) have indicated that supplementing melatonin in a dose of 1.0 mM to ram extender maintained progressive motility, intracellular ATP concentrations, DNA integrity and fertilization rate in comparison to other doses (0.001, 0.01, 0.1, and 10 mM). In contrast, Souza et al (2016) have stated that low concentration of melatonin (100 pM) increased the sperm motility, mitochondrial activity, integrity of plasma membrane and acrosome in ram semen in comparison to high concentrations (100 nM, and 100 μM). Moreover, supplementation of melatonin at low dose (0.1 mM) to semen extender of buffalo bulls maintained the ultrastructure integrity of the sperm and increased pregnancy rate in compared to control and high doses groups (0.250, 0.500, 0.750 and 1 mM) (EL-Raey et al, 2015).…”
Section: Discussionmentioning
confidence: 87%
“…Essa redução é esperada e pode ser atribuída ao declínio no metabolismo de energia dos espermatozoides que, ao serem expostos, por um longo período de incubação, acredita-se que ocorra um déficit de energia pela elevação do metabolismo celular e uma rápida utilização dos constituintes do diluente, implicando em danos diretos as organelas envolvidas na movimentação espermática, como a mitocôndria, prejudicando a atividade da cadeia de transporte de elétrons, consequentemente, provocando a redução na motilidade (Souza et al 2016b). Contudo, os resultados apresentados revelaram o sêmen com valores de motilidade espermática para garanhões, dentro do percentual exigido pelo CBRA (2013), inferindo assim, a sua aptidão para fecundação.…”
Section: Discussionunclassified
“…A integridade da membrana plasmática dos espermatozoides descongelados foi determinada pelo teste com sonda fluorescente. Para esta avaliação utilizou-se a associação de duas sondas fluorescentes, iodeto de propídio (IP) e Hoechst 33342 (H33342), conforme Souza et al (2016b). As amostras de cada tratamento foram colocadas em microtubos de 1,5mL após descongelação.…”
Section: Methodsunclassified
“…Fato esse não proporcionado pelo MEM, justificando assim a ocorrência de diferença estatística (P < 0,05) entre esses dois diluidores em todos os tratamentos. Na literatura, diversos trabalhos relataram a qualidade e eficiência do Tris Gema como diluente seminal [15,25,27,28], pois o mesmo além de atuar como uma substância tampão acarreta uma desaceleração do metabolismo da frutose pelo espermatozoide, de modo a contribuir para preservação energética da célula espermática [7]. Partindo dessa premissa, presume-se que possivelmente esse diluente seja o ideal a ser adotado em metodologias que busquem a inativação do CAEV no sêmen através de extratos naturais dissolvidos em DMSO, tornando uma ferramenta auxiliar no combate a artrite encefalite caprina.…”
Section: Discussionunclassified